Kepastian Hukum Terhadap Tidak Di Laporkan Harta Kekayaan Penyelenggara Negara Dalam Penyeleksian Calon Pimpinan Komisi Pemberantasan Korupsi - Wilson Gunawan Salim (Corruptio, 2020)
Corruption Eradication Commission (KPK) is a state institution that in carrying out its duties and authority is independent and free from the influence of any power. The Report of State Official Assets (LHKPN) is a list of all the assets of the State Administrators as outlined in the LHKPN form determined by the Corruption Eradication Commission. Selection Candidates for the leadership of the Corruption Eradication Commission are not required to submit a Report on the Wealth of State Administrators (LHKPN), the statement was said by the Chairman of the Selection Committee Yenti Garnasih. how the consequences of not considering the LHKPN (Report on the Assets of State Assets) by the KPK leadership candidate selection committee in terms of Article 29 of Law Number 30 Year 2002 concerning the Corruption Eradication Commission Jo. Article 5 of Law Number 28 of 1999 concerning State Administration that is Clean and Free of Corruption, Collusion and Nepotism relating in announcing the assets of prospective KPK leaders. The State Administrators are obliged to be willing to inspect their assets before, during and after taking office, report their assets at the first time in office, transfer, promote and retire, and to announce their assets. The purpose of making LHKPN is as part of the authority possessed by the KPK, which is to carry out steps or efforts to prevent the occurrence of other forms of corruption by registering and examining LHKPN. The report on the assets of state administrators should be enforced prior to the completion of the selection of candidates for the leadership of the Corruption Eradication Commission because this is intended as an effort to open the candidates for KPK leaders and as an effort to prevent corruption.